The Radiative–Conductive Transfer Equation in Cylindrical Geometry. Issue 5 (28th July 2016) - Ladeia, C. A.; Bodmann, B. E. J.; Vilhena, M. T. M. B.
ABSTRACT: In this work, we present a solution for the radiative–conductive transfer equation in cylinder geometry for a hollow cylinder. We discuss a semi-analytical approach to the non-linear SN problem, where the solution is constructed by Laplace transform and a decomposition method. We present the recursive scheme for the doubly discrete ordinate equation system together with physical parameter dependencies and apply the solution to test cases.